Technology transfer and foreign trade : - Tsurumi, Yoshi (Arno Press, 1980)
This book provides a detailed treatment of the new Technology Transfer Regulation of Japan. The regulation has attracted strong opposition from industry and has wide ramifications, making the need for a book on the subject all the more compelling.